2012
DOI: 10.1177/0306624x12469506
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Perpetrator Programs in Europe, Part I

Abstract: Most research on domestic violence perpetrator programs has been carried out in North America. It does not yet provide a clear picture on what works with these offenders and cannot be generalized to other cultural and legal systems. Therefore, in Part I of this article, we present the results of a survey of 54 programs that were in place in 19 European countries that addressed the programs' practice and effects. The survey captured data about program design, delivery, administration, infrastructure, and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 33 publications
(34 reference statements)
2
40
0
4
Order By: Relevance
“…Cannon et al (2016) found this model to be the primary treatment approach for 29.1% of programs, and the secondary approach for another 25%. In a European study of 54 BIPs in 19 countries, the majority (70%) indicated that they used cognitive-behavioral principles (Hamilton, Koehler, & Lösel, 2012). These interventions place emphasis on determining the function of violent behavior and typically occur in a group format (Adams, 1988).…”
Section: Psychotherapeutic and Cognitive-behavioral Therapy Modelmentioning
confidence: 99%
“…Cannon et al (2016) found this model to be the primary treatment approach for 29.1% of programs, and the secondary approach for another 25%. In a European study of 54 BIPs in 19 countries, the majority (70%) indicated that they used cognitive-behavioral principles (Hamilton, Koehler, & Lösel, 2012). These interventions place emphasis on determining the function of violent behavior and typically occur in a group format (Adams, 1988).…”
Section: Psychotherapeutic and Cognitive-behavioral Therapy Modelmentioning
confidence: 99%
“…Moreover, the researchers identifi ed some programmes in Lithuania, Poland and Slovakia, but did not receive answers from their managers/facilitators. In four countries (Bulgaria, Estonia, Hungary and Romania) authorities reported a lack of perpetrators programmes (Hamilton et al 2013(Hamilton et al : 1193. Three years later, the information about Eastern European and Baltic (male) perpetrator programmes was complemented by the results of the already mentioned IMPACT project.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, regarding the issue analysed here, they have a specific gender regime (Lewis, Ostner 1994). 4 In addition to profeminist approaches, psychodynamic and cognitive -behavioural treatments are the most popular approaches used in practical work with perpetrators in Europe (see Hamilton, Koehler, Lösel 2013: 1193. 5 Out of the Eastern European and Baltic countries presented in this paper, only countries belonging to the European Union, such as Bulgaria, the Czech Republic, Hungary, Estonia, Latvia, Lithuania, Poland, Romania and Slovakia, were taken into consideration.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Graham-Kevan (2007) discusses the lack of cohesive policy within the European Union at the time the paper was published and comments that, like with the US, the curriculum of perpetrator programs could be shaped by politics and not by evidence and science. Hamilton, Koehler and Lösel (2012) reviewed perpetrator programs that existed in practice in Europe. Their results revealed data from 19 of 23 countriesfour countries did not deliver programs.…”
Section: Perpetrator Programs In Europementioning
confidence: 99%